1993
DOI: 10.1007/bf00735915
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines induce thymidine phosphorylase expression in tumor cells and make them more susceptible to 5?-deoxy-5-fluorouridine

Abstract: The present study shows that various cytokines such as tumor necrosis factor (TNF alpha), interleukin-1 alpha (IL-1 alpha), and interferon-gamma (IFN gamma) make tumor cells much more susceptible to the cytostatic 5'-deoxy-5-fluorouridine (5'-dFUrd) than to 5-fluorouracil (5-FUra) and other cytostatics. These three cytokines increased the susceptibility of human cancer cell lines (COLO201, MKN45 and WiDr) but did not affect that of normal fibroblast WI38 cells. The cytokine mixture induced a 50-fold increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
95
0
2

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(100 citation statements)
references
References 24 publications
3
95
0
2
Order By: Relevance
“…In our series, normal/ hyperplastic prostate glands and stroma were persistently unreactive to P-GF-44C, and a strong nuclear/cytoplasmic TP expression became only apparent in areas of intense lymphocytic infiltration, probably in the context of a chronic prostatitis. Lymphocytes produce a variety of lymphokines, such as interferons and interleukins, which are potent stimulators of TP expression (Schwartz et al, 1992;Eda et al, 1993;Goto et al, 2001). Certainly, this would explain our finding that extensive lymphocytic infiltration of the prostatic tumour stroma is related with strong TP expression by cancer and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, normal/ hyperplastic prostate glands and stroma were persistently unreactive to P-GF-44C, and a strong nuclear/cytoplasmic TP expression became only apparent in areas of intense lymphocytic infiltration, probably in the context of a chronic prostatitis. Lymphocytes produce a variety of lymphokines, such as interferons and interleukins, which are potent stimulators of TP expression (Schwartz et al, 1992;Eda et al, 1993;Goto et al, 2001). Certainly, this would explain our finding that extensive lymphocytic infiltration of the prostatic tumour stroma is related with strong TP expression by cancer and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As TNF-ca has been shown to up-regulate markedly TP activity in tumour cell lines in vitro (Eda et al, 1993), the purpose of this study was to investigate whether TNF-a may be involved in the regulation of TP in vivo. To do this, we used non-neutralizing antibodies for TNF-x that recognize both unbound and receptor-bound TNF-ax to correlate the cellular distribution of TNF-a protein (both TNF-a expression by TAMs and TNF-a bound to receptors on tumour and endothelial cells) with that of TP protein expression by tumour cells in a consecutive series of primary invasive human breast carcinomas.…”
mentioning
confidence: 99%
“…Previously, we reported that both UPase and dThdPase mRNAs were upregulated by the inflammatory cytokines, INF-␥, TNF-␣ and IL-1␣. 1,2,25 Although INF-␥ upregulated the expression of both the dThdPase and UPase genes, the level of maximal induction of dThdPase was higher than that of UPase in human carcinoma cell lines. In contrast, TNF-␣ and IL-1␣ induced expression of these genes in a similar manner.…”
Section: Discussionmentioning
confidence: 98%